A CROSS-SECTIONAL STUDY OF DETERMINANTS INFLUENCING HOSPITAL SELECTION FOR PATIENTS UNDERGOING ELECTIVE GENERAL SURGERY. - Ranjan, Rajani (Student’s Journal of Health Research Africa, 2024)
Background For many patients, the decision to have elective surgery can be extremely difficult. A variety of things may influence their choice of hospital. To maximize service delivery and improve patient satisfaction, healthcare providers must have a thorough understanding of these aspects. This study aims to find and analyze the variables influencing hospital preference for patients receiving elective general surgery. Materials and Methods 200 individuals who were scheduled for elective general surgery took part in this study. Demographics, hospital-related characteristics, factors related to surgeon, hospital accreditation, infrastructure and academia were all evaluated using a standardised questionnaire. Results The surgeon’s competence (93%), attitude toward patients (90%), and cost-effectiveness (86%) were the most important variables influencing hospital choice. Additionally, significant were knowing the hospital well (73%) and prior repute of the hospital (76%). Patient choices were affected by the hospital’s infrastructure (70%) and accreditation (56%). Conclusion The three most important factors influencing hospital choice for elective procedures are cost effectiveness, surgeon skill, and patient experience. Hospital amenities and reputation are also very important. By being aware of these elements, hospital managers can increase patient satisfaction and draw in new patients. Recommendation High clinical care standards, cost, and improving patient experience through better facilities and communication should be the key priorities of hospital management. It is also crucial to make an effort to establish and preserve a favourable reputation for the institution.